Involvement in sports activities among school and University students - Gošnik, J., Ćurković, S. (Array, 2008)
Researches indicate that majority of students stop doing sports between the ages of 14 and 18. Based on the results of the research we conducted a survey with the aim of identifying sports activities students had taken part in prior to their enrollment at the university, as well as determining the level of their involvement in these activities, and finding out it they were, and to which extent, still involved in these activities after their enrollment at the university. We wanted to estimate how many students continue doing sports during their studies at the university. The survey was conducted on 894 first year students of the University of Zagreb in academic year 2007-08- (24.6% male and 75.4% female) who were given an anonymous questionnaire. Results showed that 21.4% students (16.4% male and 23% female) hadn't taken part in any sports activities prior to the enrollment at the university. Analysis with regard to gender revealed that majority of male students had been playing football (22.3%), basketball (13.6%), tennis (7.3%), handball (3.6%), table tennis (3.6%) and athletics (2.7%). Majority of female students had been dancing (5.9%), swimming (3.7%) playing volleyball (12.6%), handball (8.6%), basketball (8, 00%) athletics (5.6%). After the enrollment at the university the number of students who stopped taking part in the sports activities tripled (64.9% - 54.1% male students, 68.4% female students). The results of the survey also revealed that at the moment they were taking part in fewer sports activities than earlier. Football is the most popular sport among university students (17.3% of students play it), basketball (6.8%), tennis (4.5%) and cycling (3, 6%). The survey indicates that there is a high percentage of female students who stop taking part in sports activities. Sports activities majority of female students currently take part in are: dancing (5.2%), cycling (3.7%) and volleyball (2.7%). It seems that dancing is the only activity that girls have constantly been involved with, while the number of students taking part in other activities has reduced. Conclusion: our survey joins a group of surveys indicating that the number of students who stop taking part in sports activities after finishing secondary school and enrolling at a university is high. The reasons for this need to be researched further, while the attention should be paid to ways of motivating students to persevere with recreational physical activity, which is the best guarantee of healthy life.